Magnetosphere and Solar Winds, Humans and Communication - Essa, Khalid S.; Mahmoud, Khaled H.; Chemin, Yann-Henri (IntechOpen, 2022)
Magnetosphere and Solar Winds, Humans and Communication consists of ten chapters organized into two sections. The first section presents a full description of the magnetosphere and its effect on the solar wind, climatic modes, the Polar Cap index in relation to magnetosphere disturbances (substorms and magnetic storms), recent developments and challenges in developed ionosphere models, and more. The second section discusses solar flux, solar proton activity over the solar cycle, temporal variation of the sun's activity, and macroscopic scales of spin.